Additional value of magnetic resonance-targeted biopsies to standard transrectal ultrasound-guided biopsies for detection of clinically significant prostate cancer. (4th March 2017) - von Below, Catrin; Wassberg, Cecilia; Norberg, Mona; Tolf, Anna; Kullberg, Joel; Ladjevardi, Sam; Häggman, Michael; Bill Axelson, Anna; Ahlström, Håkan
Abstract: Objective: The aim of this study was to evaluate the additional value of magnetic resonance imaging-targeted biopsy (MRI-TB) to standard transrectal ultrasound-guided biopsy (SB) for detection of clinically significant prostate cancer (PCa). An additional aim was to compare the biopsy results to MRI evaluation using a Likert scale. Materials and methods: Patients with newly diagnosed localized PCa ( n = 53) by clinical routine SB were prospectively included. The majority of the patients were scheduled for curative therapy before enrollment. The patients underwent multiparametric MRI (mpMRI) at 3 T using an endorectal coil followed by two MRI-TBs, using ultrasound with cognitive fusion. All included patients underwent MRI-TB, even those who had low to very low suspicion of significant PCa on mpMRI. The detection rate of significant cancer on SB versus SB + MRI-TB was compared in the 53 included patients and with whole-mounted histopathology as reference in 34 cases. Comparison of the biopsy results to MRI evaluation and interreader agreement calculation of five-point Likert score evaluation were performed. Results: In total, 32 significant (Gleason ≥7) PCa were detected by SB, while SB + MRI-TB detected an additional five significant PCa. MRI-TB alone detected 20 and missed 17 significant PCa. Ten of the significant PCa cases missed by MRI-TB had a Likert score of 3 or lower. Interreader agreement using the Likert scale was high, with a kappa value of 0.77 (95% confidence interval 0.63–0.92, p < 0.0001). Conclusion: Detection of significant PCa increased by adding MRI-TB to SB. This may not be of enough clinical value to justify the use of targeted biopsies in this patient group.